An Alum-Free Jellyfish Treatment for Food Applications - Bleve, Gianluca; Ramires, Francesca Anna; De Domenico, Stefania; Leone, Antonella (Frontiers in Nutrition, 2021)
Jellyfish traditionally produced by using salt and alum mixtures are consumed and marketed as food in Asian and South-Eastern Countries. In the last years, Western consumers are increasing their attention in jellyfish (JF) as food source. JF derived food in Europe (EU) are regulated by the novel food law, but methods for JF treatment and processing have not been developed yet. In the present study, a protocol for the stabilization and processing of JF into semi-finished food products without the use of alum was proposed for the first time. Safety and quality parameters, together with a series of technological and nutritional traits were used for the process monitoring and the characterization of the JF obtained products. Calcium lactate (E327), calcium citrate (E333) and calcium acetate (E263), which are food thickening/stabilizing agents allowed by EU regulations, were able to control the presence of possible microbial pathogens and spoilage species. The increase in texture and in nutritional traits, such as antioxidant activity, protein and fatty acids content, was obtained. For the first time, the application of phenolic compounds for improving JF technological and nutritional features was verified. This study launches a new procedure for making JF products suitable for human consumption in Western Countries.